Komunikasi NonVerbal Dalam Praktik Peradilan Pidana Dengan Kewenangan Melakukan Interpretasi Hukum - Rocky Marbun (Fakultas Hukum, Universitas Warmadewa, 2021)
The logical consequence of submitting to the civil law system - one of which is paper working or administrative mindedness. As characterized by Article 75 of the Criminal Procedure Code, that is, every legal action must be in the form of an Investigation Report (BAP). Thus, a BAP is a legal document that contains information for Law Enforcement Officials (APH) to obtain a description of a criminal event. Normative Legal Studies, in essence, focus on APH activities to interpret legal documents in order to be able to bring up a legal decision. Thus, legal practitioners and academics forget about the ability of APH as an ordinary human being who can build a non-verbal communication in relation to the legal decisions it will make. Therefore, this study focuses on a form of non-verbal communication that has an influence on the praxis realm of legal science, namely by asking the problem is